OSC2 and CYP716A14v2 Catalyze the Biosynthesis of Triterpenoids for the Cuticle of Aerial Organs of Artemisia annua. Issue 1 (9th January 2015) - Moses, Tessa; Pollier, Jacob; Shen, Qian; Soetaert, Sandra; Reed, James; Erffelinck, Marie-Laure; Van Nieuwerburgh, Filip C.W.; Vanden Bossche, Robin; Osbourn, Anne; Thevelein, Johan M.; Deforce, Dieter; Tang, Kexuan; et al.
Abstract : Comparative RNA-seq analysis of glandular and filamentous trichomes from Artemisia annua reveals the biosynthesis pathway to 3-oxo triterpenes that accumulate in the cuticular wax of A. annua 's aerial organs. Abstract: Artemisia annua is widely studied for its ability to accumulate the antimalarial sesquiterpenoid artemisinin. In addition to producing a variety of sesquiterpenoids, A. annua also accumulates mono-, di-, and triterpenoids, the majority of which are produced in the glandular trichomes. A. annua also has filamentous trichomes on its aerial parts, but little is known of their biosynthesis potential. Here, through a comparative transcriptome analysis between glandular and filamentous trichomes, we identified two genes, OSC2 and CYP716A14v2, encoding enzymes involved in the biosynthesis of specialized triterpenoids in A. annua . By expressing these genes in Saccharomyces cerevisiae and Nicotiana benthamiana, we characterized the catalytic function of these proteins and could reconstitute the specialized triterpenoid spectrum of A. annua in these heterologous hosts. OSC2 is a multifunctional oxidosqualene cyclase that produces α-amyrin, β-amyrin, and Δ-amyrin. CYP716A14v2 is a P450 belonging to the functionally diverse CYP716 family and catalyzes the oxidation of pentacyclic triterpenes, leading to triterpenes with a carbonyl group at position C-3, thereby providing an alternative biosynthesis pathway to 3-oxo triterpenes. Together, these enzymes produce specialized triterpenoids that are constituents of the wax layer of the cuticle covering the aerial parts of A. annua and likely function in the protection of the plant against biotic and abiotic stress.